REPERTOIRE DALAM THE GREAT GATSBY KARYA F. SCOTT. FITZGERALD: ANALISIS RESPONS ESTETIK WOLFGANG ISER - Nurul Wahidah (PENAOQ: Jurnal Sastra, Budaya dan Pariwisata, 2020)
The arising of literature in America have been influenced by few improvement and development its landscape. The alteration takes a part of American society till twentieth century. The condition of society is scene of the set experiences and knowledge which is filling in the prose. One of American literature shows the correlation between social fact, history, and culture as reality phenomena and fiction or novel as imaginary world which is The Great Gatsby by F. Scott. Fitzgerald. Thereby, to express all of the realities or facts and to see what extent the fiction represents about reality or fact. From this, it needs a research. This research entitled: “Repertoire in F. Scott. Fitzgerald’s The Great Gatsby: Analysis of Response Aesthetic Wolfgang Iser”. The aim of this research is to express the form of repertoire in TGG which is background of its created. So the foreground of the author’s purposes can be actualized. Beside, this analysis also appears effect to build a response aesthetic with repertoire in the text and it belongs to the reader. In this research uses the entire whole repertoire in the texts which is known in the novel, TGG as an object of study and the repertoire as a perspective of Wolfgang Iser theory. Afterwards, this object will be linked with all of the nature of the work itself, include social norm or fact, history and the whole of culture that involve to the text which is emerged. After reading process, read, and to conducted analysis data. From the act of analyses, the social norm can be reveal in The Great Gatsby is a social reality of American society which is not release from the spirit of American Dream, group of society; upper class and lower class. Then, other social norms are material achievement, business and the lack of morality. The cultural fact that emerged in this novel is dance party and the roar of jazz music. The last one is the fact of history which is known in the TGG is a Post-World War One. Starting from the background and the response aesthetic, foreground that will be turn of the author is a social fact, which is revealed to protest or t critic of the concept of the American Dream.